Auditoría integral aplicada a las cooperativas de ahorro y crédito y la repercusión en su sostenibilidad - Pérez Vera, Ana Jacqueline (2020)
The present investigation entitled: Integral audit applied to cooperatives of saving and credit (COAC) and the repercussion on their sustainability, describes the way in which the integral audit has an impact on the sustainability of the COAC. Within this context, and considering the regulatory changes issued since 2011 and due to the fact that in the last seven years the liquidation of around 242 COAC, mainly in segment 5, was observed, the need to make a contribution to the solution was determined of this problem using the knowledge and experiences acquired in the field of Auditing. Along, these lines, this document sets out the theoretical and legal frameworks that served as the basis and foundation for the development of investigation, using a qualitative and quantitative approach, by carrying out activities that were carried out in the field, obtaining information documentary and making observations to the processes executed by the COAC….....